REPEATED SPRINT ABILITY IN PROFESSIONAL SOCCER vs. PROFESSIONAL FUTSAL PLAYERS [Capacidad de realizar esprints repetidos en jugadores profesionales de fútbol vs. Fútbol sala] - V. Cuadrado-Peñafiel; J. Párraga-Montilla; M.A. Ortega-Becerra; P. Jiménez-Reyes (Federación Extremeña de Balonmano; University of Extremadura, 2014)
Purpose: To investigate the changes through repeated explosive effort sequences (20+20-m sprint with change of direction), jumping, metabolic response (lactate), as well as the relationship between these variables and fitness qualities (strength and endurance) in professional futsal and soccer players. Methods: Male players (n =30, Twelve futsal and twenty soccer players) completed three testing sessions. In the first session was measured VO2max on a motorized treadmill. In the second session was measured counter movement jump (CMJ) and full squat RM in Smith Machine. Finally, in the third session six repeated-explosive effort sequences (RES) was performed. Results: Similar values of lower limbs strength, CMJ height, LAC after RSA test and VO2max (95,12 vs. 94,73; 34,5 vs. 35,9; 13,65 vs. 14,33; 62,78 vs. 62,95 soccer vs. futsal respectively) and significant differences when are analysed the loss of performance in velocity (total and between three first and three last) and vertical jump height (2,67 vs. 4,4**; 1,28 vs. 2,1*; 2,88 vs. 6,1**; 9,71 vs. 14,3* soccer vs. futsal respectively). Conclusions: Professional futsal and soccer obtain significant differences in speed and vertical jump height (CMJ) loss despite having similar values in squat, oxygen consumption, lactate after RSA test and CMJ height. Issue that could be attributed to the characteristics of the sport. This suggests that the volume should be increased oriented ability to perform repeated sprint actions over other type of training aimed at improving aerobic capacity especially at professional level.